Money Politic In Elections: Islamic Law Perspective - Syahrul Mokodompis; Rosdalina Bukido; Delmus Puneri Salim; Misbahul Munir Makka (Jurnal Ilmiah Al-Syir'ah, 2018)
Money is the most needed resource by people, becoming a reference for each transaction or individual maneuver and as a medium of exchange.Money is an urgent factor that is useful to boost one's personal power and to control the strategic discourse associating with a political interest and power.The nomination process is often inseparable from the use of money to attract the sympathy of citizens.Supposedly, the candidates should not rely on money politic as a way to win the election, but they must demonstrate their ability to be representative of the people. This research is a qualitative study. It was located in Sangtombolang District, Bolaang Mongondow Regency, North Sulawesi. The data obtained were processed and verified in order to obtain descriptive findings of money politic in the election perspective of Islamic law. The practice of money politic occurred in some people due to ignorance of the law on money politic, habits, and economic urgency. In Islamic values,money politicor risywah is something that is given to cancel the truth and to justify the falsehood,risywah in Islamic law is considered as confiscation of other people's property, as mentioned in Surah Al Baqarah verse 188. MUI also explained that people who give and receive risywah are haram (forbidden). Keywords: Money politic; election; Islamic law